Haji Muhammad Yassin Mosque Building Inspection using Unmanned Aerial Vehicle (UAV) - Subli, Syakir; Sarif, Abd Sukor (Progress in Engineering Application and Technology, 2024)
In the field of civil engineering, UAVs can serve as tools for building inspection processes, including mapping areas, monitoring work progress, inspecting tall structures, and identifying defects and cracks. One major challenge in building inspections involves reaching roofs, tall walls, and other inaccessible exteriors. Current methods, like rope access and scaffolding, are both risky and have significant costs and time. These approaches may restrict the capacity to observe and collect detailed data from certain areas of the building. The mosque also has a ceiling leaked near the dome area, which cause water dripping to the carpet at the main prayer hall. This study aim’s conduct an inspection on the minaret, roof and the building façade of Haji Muhammad Yassin Mosque by a UAV. To conduct the inspection, DJI Mini 2 SE drone is used. Next, all the images are processed using Adobe Photoshop and analyzed by using CSP 1 Matrix. Out of 89 data analyzed, 54 were green (60.67%) and 35 were yellow (39.33%). The overall building score is 4.303, indicating that the overall condition of Haji Muhammad Yassin Mosque is good. Although the building condition is good, there is one defect on image 60 where the matrix score almost reach to red colour. This defect needs to be address quickly to avoid the defect becoming much worse. The inspection was successfully achieved its objectives even with an entry-level drone like the DJI Mini 2 SE. The inspection followed the JKR Guidelines for Inspection and Assessment of Existing Building Conditions In short, this study has produced the data about the defect on the mosque. In a nutshell, this study could help future developments in building inspection using UAV.